The Impact of the COVID-19 Pandemic on Head and Neck Cancer Diagnosis in the Piedmont Region, Italy: Interrupted Time-Series Analysis - Popovic, Maja; Fiano, Valentina; Moirano, Giovenale; Chiusa, Luigi; Conway, David I.; Garzino Demo, Paolo; Gilardetti, Marco; Iorio, Giuseppe Carlo; Moccia, Chiara; Ostellino, Oliviero; Pecorari, Giancarlo; Ramieri, Guglielmo; et al. (Frontiers in Public Health, 2022)
The COVID-19 pandemic has likely affected the most vulnerable groups of patients and those requiring time-critical access to healthcare services, such as patients with cancer. The aim of this study was to use time trend data to assess the impact of COVID-19 on timely diagnosis and treatment of head and neck cancer (HNC) in the Italian Piedmont region. This study was based on two different data sources. First, regional hospital discharge register data were used to identify incident HNC in patients ≥18 years old from January 1, 2015, to December 31, 2020. Interrupted time-series analysis was used to model the long-time trends in monthly incident HNC before COVID-19 while accounting for seasonal fluctuations in the HNC admissions. Second, in a population of incident HNC patients eligible for recruitment in an ongoing clinical cohort (HEADSpAcE) that started before the COVID-19 pandemic, we compared the distribution of early-stage and late-stage diagnoses between the pre-COVID-19 and the COVID-19 period. There were 4811 incident HNC admissions in the 5-year period before the COVID-19 outbreak and 832 admissions in 2020, of which 689 occurred after the COVID-19 outbreak in Italy. An initial reduction of 28% in admissions during the first wave of the COVID-19 pandemic (RR 0.72; 95%CI:0.62-0.84) was largely addressed by the end of 2020 (RR 0.96; 95%CI:0.89-1.03) when considering the whole population, although there were some heterogeneities. The gap between observed and expected admissions was particularly evident and had not completely recovered by the end of the year in older (≥75 years) patients (RR: 0.88, 95%CI:0.76-1.01), patients with a Romano-Charlson comorbidity index below 2 (RR 0.91; 95%CI:0.84-1.00), and primary surgically treated patients (RR 0.88; 95%CI:0.80-0.97). In the subgroup of patients eligible for the ongoing active recruitment, we observed no evidence of a shift towards a more advanced stage at diagnosis in the periods following the first pandemic wave. The COVID-19 pandemic has affected differentially the management of certain groups of incident HNC patients, with more pronounced impact on older patients, those treated primarily surgically, and those with less comorbidities. The missed and delayed diagnoses may translate into worser oncological outcomes in these patients.